ASYMMETRIC LEAVES1 and auxin activities converge to repress BREVIPEDICELLUS expression and promote leaf development in Arabidopsis. - Hay, A; Barkoulas, M; Tsiantis, M (2006)
Leaf development in higher plants requires the specification of leaf initials at the flanks of a pluripotent structure termed the shoot apical meristem. In Arabidopsis, this process is facilitated by negative interactions between class I KNOTTED1-like homeobox (KNOX) and ASYMMETRIC LEAVES1 (AS1) transcription factors, such that KNOX proteins are confined to the meristem and AS1 to leaf initials. Sites of leaf inception are also defined by local accumulation of the hormone auxin; however, it is unknown how auxin and AS1 activities are integrated to control leaf development. Here, we show that auxin and AS1 pathways converge to repress expression of the KNOX gene BREVIPEDICELLUS (BP) and thus promote leaf fate. We also demonstrate that regulated auxin gradients control leaf shape in a KNOX-independent fashion and that inappropriate KNOX activity in leaves perturbs these gradients, hence altering leaf shape. We propose that regulatory interactions between auxin, AS1 and KNOX activities may both direct leaf initiation and sculpt leaf form.